Prevalence of shigellosis diarrhoea in a paediatrics population: hospital based survey in Bangui, Central African Republic. - (:unkn) unknown (My University, 2010)
INTRODUCTION: Shigellosis is still a major public health problem in sub-Saharan countries, especially among children. METHODOLOGY: The prevalence of shigellosis in children presenting with diarrhoea in the Complexe Pédiatrique de Bangui, Central African Republic, was determined. Stools were analyzed in the bacteriology laboratory of the Institut Pasteur de Bangui, Central African Republic, where identification of Shigella species and analysis of antibiotics susceptibility were performed. RESULTS: A total of 15 strains of Shigella were isolated from 156 stools; Shigella flexneri was the only species found. Two infected children died of dehydration. Most strains were resistant to antibiotics except quinolones, which were active on all of these strains. CONCLUSIONS: The control of Shigella infections should be reinforced in Bangui, and accurate, affordable and rapid methods of diagnosis would be helpful.
Keywords: African Research